تطبيق طريقة إعطاء الواجبات في تعليم اللغة العربية خارج الشبكة لمحدودية الوصول الرقمي بالمدرسة الثانوية الحكومية 1 إندراغيري هيلير رياو - Ria Deni; Fajriyani Arsya; Eka Rizal (Qawa’id: Jurnal Bahasa dan Sastra Arab, 2026)
This study aims to analyze the implementation of the recitation method in offline (luring) Arabic language learning and the perceptions of eighth-grade students at Madrasah Tsanawiyah Negeri 1 Indragiri Hilir. Arabic learning requires comprehensive understanding; however, limited face-to-face instruction time led to less effective material transfer due to the lack of direct explanation from the teacher. Therefore, the recitation method is applied to optimize learning. This research employs a qualitative descriptive approach. The instruments used to collect data were interviews with the subject teacher and questionnaires distributed to the students. The data analysis technique followed the Miles and Huberman model, consisting of three activities: data reduction, data display, and conclusion drawing/verification. The findings indicate that the application of the recitation method was carried out through three main stages: the assignment giving stage, the assignment execution stage, and the evaluation stage. Most of these stages have been well-implemented in offline Arabic learning. However, teachers could not monitor students' task completion fully outside of school hours, and constraints were found in the lack of focus and attention of some students in completing Arabic assignments independently.